A bibliometric analysis of diets and breast cancer research - Kotepui M. (Asian Pacific Organization for Cancer Prevention, 2014)
Breast cancer is the most common cancer among women worldwide. The primary aim of this work was to provide an in-depth evaluation of research publications in the field of diets and breast cancer. The impact of economic outcome on national academic productivity was also investigated. Data were retrieved using Pubmed for English-language publications. The search included all research for which articles included words relating to "diets and breast cancer". Population and national income data were obtained from publicly available databases. Impact factors for journals were obtained from Journal Citation Reports® (Thomson Scientific). There were 2,396 publications from 60 countries in 384 journals with an impact factor. Among them, 1,652 (68.94%) publications were Original articles. The United States had the highest quantity (51% of total) and highest of mean impact factor (8.852) for publication. Sweden had the highest productivity of publication when adjusted for number of population (6 publications per million population). Publications from the Asian nation increased from 5.3% in 2006 to 14.6% in 2012. The Original article type was also associated with geography (p<0.001; OR=2.183; 95%CI=1.526-3.123), Asian countries produced more proportion of Original articles (82%) than those of rest of the world (67.6%). Diets and breast cancer-associated research output continues to increase annually worldwide including publications from Asian countries. Although the United States produced the most publications, European nations per capita were higher in publication output.